Identify critical success factors to implement integrated green and Lean Six Sigma. Issue 4 (3rd December 2018) - Mishra, Mrigendra Nath
Abstract : Purpose: The purpose of this paper is analysis of Green and Lean Six Sigma, based on the success factors in its use through a well thought-out literature review, is being planned; a framework has been integrated in a productive manner with the Green and Lean and Six Sigma methods so as to incorporate and actualize the execution. Design/methodology/approach: The methodology consists of comparative investigation of Green, Lean management and Six Sigma using open written work, essential analysis at data and master experience of the researchers. To achieve this goal, a significant review of the existing literature of the subject area has been done to prepare a framework in view of the critical success factors. A study was arranged and flowed survey from various businesses utilizing John's Macintosh Project (JMP) statistical software. Findings: The paper establishes the distinguishing proof of five success factors with their situational importance and shows that the integrated Green and Lean Six Sigma can drive the organizations to optimize their resources and cost of services or productions. Practical implications: A Green and Lean Six Sigma organization would take profits by the use of the proposed framework in an alternate extent of organizations should be dynamic. The organizations should assess their shortcomings and qualities, set needs and perceive objectives for fruitful implementation. Originality/value: Suggestions are being made regarding thoughts and methods that would constitute a Green and Lean Six Sigma organization. The suggested framework compare the method for improvements that may occur in organizations while implementation of the Green and Lean management or Six Sigma.